Analisis Penggunaan Cerita Rakyat Bengkulu Dalam pembelajaran Retorika/Komunikasi Massa - Kurniawan, Rio; Yulistyo, Didi (ESTETIK : Jurnal Bahasa Indonesia, 2018)
The purpose of this study is to trace the extent of the use of Bengkulen folklore in the process of teaching and learning rhetorical subject. The study is a descriptive research which tries to portray the exercise of teaching rhetorical subject in which Bengkulen folklore is included. This study applies qualitative approach. The research subject deals with the fifth semester students of class A from the study program of Indonesian Language Teaching (FKIP) of Bengkulu University in the academic year of 2016-2017. The study results in that student activities change into positive direction in learning by folklore. The application of folklore to the students can improve their skill in rhetoric or public communication. It can be seen from the grades they achieve and the extent of their finishing the subject. Based on the data analyzed, the result shows that there 21 students who receive grade up 70 and their fulfillment in learning reaches 90, 84%.